2017
DOI: 10.1111/nin.12227
|View full text |Cite
|
Sign up to set email alerts
|

Rationing nurses: Realities, practicalities, and nursing leadership theories

Abstract: In this paper, we examine the practicalities of nurse managers' work. We expose how managers' commitments to transformational leadership are undermined by the rationing practices and informatics of hospital reform underpinned by the ideas of new public management. Using institutional ethnography, we gathered data in a Canadian hospital. We began by interviewing and observing frontline leaders, nurse managers, and expanded our inquiry to include interviews with other nurses, staffing clerks, and administrators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…For instance, the statement I admit my mistakes to others (item_16), which was originally a part of the relational transparency, was qualified into the moral processing subscale. The above‐mentioned observations support the thesis about the need to develop a model of authentic leadership dedicated to nursing, which would consider rationing nursing care (Fast & Rankin, ) and patient safety (Agnew et al., ; Dirik & Seren Intepeler, ; Perry, ; Stewart & Usher, ). Such a model can be important for in improving the curricula of pre‐ and postgraduate courses.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, the statement I admit my mistakes to others (item_16), which was originally a part of the relational transparency, was qualified into the moral processing subscale. The above‐mentioned observations support the thesis about the need to develop a model of authentic leadership dedicated to nursing, which would consider rationing nursing care (Fast & Rankin, ) and patient safety (Agnew et al., ; Dirik & Seren Intepeler, ; Perry, ; Stewart & Usher, ). Such a model can be important for in improving the curricula of pre‐ and postgraduate courses.…”
Section: Discussionsupporting
confidence: 57%
“…For nurse managers, the challenge is to align service targets with looking after the safety of the nurse and the patient. Fast and Rankin (2018) showed that ‘nurse managers’ consciousness is being bifurcated—what they know from experience, from being there, is overruled by authoritative institutional information’ (p. 8). Supporting this view, Hegney et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although several participants claimed to draw upon a transformational leadership approach their descriptions of leadership failed readily to match up with key theoretical constructs of transformational theory. Moreover, it is also argued that the day-to-day demands of community nursing and the systems within which these operate, effectively subsume even the best leadership intentions of those working in the field, precluding the successful operation of a model such as that of transformational leadership (Fast & Rankin, 2018). For such reasons Hutchinson and Jackson (2013) argue that, in contrast to the critical examination of leadership found elsewhere, within nursing there has been too much reliance on theories that do not readily reflect nursing in practice: what is needed is a different understanding of nursing leadership that is 'cognisant of the complexities and challenges of the healthcare environment'.…”
Section: Community Nursing Leadershipmentioning
confidence: 99%
“…This relational approach has positive impacts on positive outcomes for patients and staff (Asif et al 2019;Boamah, et al 2018). However, the challenges encountered in District Nursing Leadership settings where the day-to-day demands of service provision are not readily compatible with principles of transformational leadership make such leadership very difficult to achieve (Fast & Rankin, 2018). It is for such reasons that previous writers have argued for a model of nursing leadership that takes greater account of the challenges that nurses do face in everyday provision of care (Hutchinson & Jackson, 2013).…”
Section: District Nursing Leadershipmentioning
confidence: 99%